Carbohydrate feedings before, during, or in combination improve cycling endurance performance - Wright, D. A.; Sherman, W. M.; Dernbach, A. R. (Journal of Applied Physiology, 1991)
This study examined the effects of no carbohydrate (PP), preexercise carbohydrate feeding (CP), carbohydrate feedings during exercise (PC), and the combination of carbohydrate feedings before and during exercise (CC) on the metabolic responses during exercise and on exercise performance. Nine well-trained cyclists exercised at 70% of maximal O2 uptake until exhaustion. Blood glucose peaked 30 min after the preexercise carbohydrate feeding and at the start of exercise was 25% below the prefeeding concentration (4.76 mM). At exhaustion, glucose had declined to 3.8 (PP), 4.0 (CP), 4.6 (PC), and 5.0 mM (CC). Insulin was 300% above basal (7 microU/ml) at the start of exercise for CC and CP and returned to baseline by 120 min of exercise. When carbohydrates were consumed, the rate of carbohydrate oxidation was significantly higher throughout exercise than during PP. Total work produced during exercise was 19-46% (P less than 0.05) higher when carbohydrates were consumed. Time to exhaustion was 44% (CC), 32% (PC), and 18% (CP) greater than PP (201 min; P less than 0.05). Performance was improved by ingestion of carbohydrates before and/or during exercise; performance was further improved by their combination. This is probably the result of enhanced carbohydrate oxidation, especially during the later stages of exercise.